Remaking the Chinese empire : Manchu-Korean relations, 1616-1911 - Wang, Yuanchong, 1979- (Cornell University Press, 2018)
"This book explores China's transformation from an empire into a modern state through the lens of Sino-Korean political relations during the last imperial dynasty in Chinese history"--